Comparison of Antimicrobial Susceptibility of Urogenital Neisseria gonorrhoeae Isolates Obtained From Women and Men. Issue 8 (August 2015) - Kidd, Sarah; Moore, Page C.; Kirkcaldy, Robert D.; Philip, Susan S.; Wiesenfeld, Harold C.; Papp, John R.; Kerndt, Peter R.; Venkatasubramanian, Lalitha; Ghanem, Khalil G.; Hook, Edward W.
Abstract : Background: The US system for gonococcal antimicrobial susceptibility surveillance monitors trends exclusively among men with urethral infection, the population from whom the yield of gonococcal culture is highest. Little is known about the susceptibility of female urogenital isolates, and it is unclear whether gonococcal susceptibility among men who report sex exclusively with women (MSW) is representative of susceptibility among women. Methods: Using isolates collected during a recent treatment trial in 5 US cities, we performed a secondary analysis to compare antimicrobial susceptibilities of Neisseria gonorrhoeae urogenital isolates obtained from women, MSW, and men who have sex with men (MSM). Pretreatment isolates were collected from trial participants; minimum inhibitory concentrations (MICs) were determined by agar dilution. Geometric mean MICs were adjusted for geographic location using general linear models. Results: Susceptibility data for urogenital isolates from 56 women, 252 MSW, and 170 MSM were studied. The adjusted geometric mean ceftriaxone MIC was similar among women (0.0067 μg/mL; 95% confidence interval [CI], 0.0049–0.0092 μg/mL) and MSW (0.0060 μg/mL; 95% CI, 0.0053–0.0066 μg/mL). In contrast, the adjusted geometric mean ceftriaxone MIC was higher among MSM (0.0098 μg/mL; 95% CI, 0.0082–0.0119 μg/mL) than among MSW. This same pattern was observed for other antimicrobials, including cefixime and azithromycin Conclusions: Ceftriaxone, cefixime, and azithromycin MICs were higher among MSM than among MSW, but were similar among women and MSW. These findings suggest that gonococcal antimicrobial susceptibility surveillance based on urethral isolates from MSW may adequately represent susceptibility of urogenital N. gonorrhoeae in women. Abstract : A comparison of the antimicrobial susceptibility of urogenital gonococcal isolates obtained from women, men who have sex exclusively with women, and men who have sex with men found that susceptibility among women did not differ from that among men who have sex exclusively with women.